2023
DOI: 10.3389/fbioe.2023.1118911
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a ternary component chip with enhanced desorption efficiency for laser desorption/ionization mass spectrometry based metabolic fingerprinting

Abstract: Introduction:In vitro metabolic fingerprinting encodes diverse diseases for clinical practice, while tedious sample pretreatment in bio-samples has largely hindered its universal application. Designed materials are highly demanded to construct diagnostic tools for high-throughput metabolic information extraction.Results: Herein, a ternary component chip composed of mesoporous silica substrate, plasmonic matrix, and perfluoroalkyl initiator is constructed for direct metabolic fingerprinting of biofluids by lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…As one of the critical factors determining LDI efficiency, which is associated with enhanced intensity of the MS signal, thermal-driven desorption has gained significant attention. In detail, ionization assistant reagents with low thermal conductivity can induce local heat confinement upon laser irradiation more efficiently, leading to a higher ion-desorption efficiency. ,,, Recently, Cheng and Ng showed that the desorption process can also be highly influenced by the extent of hole generation. , Specifically, desorption can be facilitated by electrostatic repulsion between positively charged analytes and holes generated on the substrate surface upon laser irradiation (i.e., charge-driven desorption) …”
Section: Resultsmentioning
confidence: 99%
“…As one of the critical factors determining LDI efficiency, which is associated with enhanced intensity of the MS signal, thermal-driven desorption has gained significant attention. In detail, ionization assistant reagents with low thermal conductivity can induce local heat confinement upon laser irradiation more efficiently, leading to a higher ion-desorption efficiency. ,,, Recently, Cheng and Ng showed that the desorption process can also be highly influenced by the extent of hole generation. , Specifically, desorption can be facilitated by electrostatic repulsion between positively charged analytes and holes generated on the substrate surface upon laser irradiation (i.e., charge-driven desorption) …”
Section: Resultsmentioning
confidence: 99%
“…In addition, we conducted experiments to demonstrate the enhanced photothermal conversion in Vo‐Co‐2, using the chemical thermometer benzyl pyridinium ion (BP) as the indicator. [ 27 ] As shown in Figure S21 (Supporting Information), compared with Co 3 O 4 , Vo‐Co‐1, and Vo‐Co‐3, Vo‐Co‐2 displayed a higher desorption efficiency under the same laser intensity, and its thermal‐driven desorption was enhanced the most. The results suggested that an appropriate amount of oxygen vacancies induces enhanced thermal‐driven desorption, consistent with the higher photothermal conversion of Vo‐Co‐2 (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of Thermometer Molecules: The synthesis of BP followed a method reported in ref. [27] Typically, 100 μL of benzyl chloride was added to 2 mL pyridine. Then, the mixture was stirred at 60 °C for 5 h in a 25 mL round-bottomed flask.…”
Section: Synthesis Of Co-mofmentioning
confidence: 99%